Property requirements for liquid rocket propellants - Goodger, E. M. (College of Aeronautics, 1959)
An analysis is made of the properties necessary for liquid rocket propellants to give effective performance with acceptable handling. Typical propellants are examined against this requirement background, and their relative suitability assessed.